2015
DOI: 10.1021/acs.nanolett.5b00584
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Templated Surface Nanopatterning of Chalcogenide Thin Films: A Novel Approach Toward Solar Cells with Enhanced Efficiency

Abstract: Concepts of localized contacts and junctions through surface passivation layers are already advantageously applied in Si wafer-based photovoltaic technologies. For Cu(In,Ga)Se2 thin film solar cells, such concepts are generally not applied, especially at the heterojunction, because of the lack of a simple method yielding features with the required size and distribution. Here, we show a novel, innovative surface nanopatterning approach to form homogeneously distributed nanostructures (<30 nm) on the faceted, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
119
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 109 publications
(137 citation statements)
references
References 31 publications
18
119
0
Order By: Relevance
“…[25] It was found that similar to a KF PDT, a surface layer forms. [5][6][7][8][9]26,30] Additionally, as presented here for a RbF PDT, with the introduction of a KF PDT, a blocking of the diode current was observed. [15] Recently, Malitckaya et al calculated the bandgap energies of AlkInSe 2 (Alk = Li, Na, K, Rb, Cs) secondary phases, which are expected to segregate on the surface of the CIGS absorber for K, Rb, and Cs.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…[25] It was found that similar to a KF PDT, a surface layer forms. [5][6][7][8][9]26,30] Additionally, as presented here for a RbF PDT, with the introduction of a KF PDT, a blocking of the diode current was observed. [15] Recently, Malitckaya et al calculated the bandgap energies of AlkInSe 2 (Alk = Li, Na, K, Rb, Cs) secondary phases, which are expected to segregate on the surface of the CIGS absorber for K, Rb, and Cs.…”
Section: Discussionsupporting
confidence: 68%
“…Initially, it was found that the KF PDT causes the Cu depletion of the CIGS surface [4] and that a K-In-Se phase forms. [5][6][7][8] Additionally, shown in Figure 1f. A barrier at the front contact is introduced originating from a conduction band offset ΔE C at the iZnO/CdS interface.…”
Section: Introductionmentioning
confidence: 99%
“…Even for an ideal PL, V oc and η don't catch up to the same values. This can be explained by the fact that no perfect passivation of the defects is assumed here, unlike Reinhard et al [10], who modeled the interface between PL and CIGSe without any defects. It is very noteworthy that a significant improvement also occurs for a device having initially a very small interface recombination rate, the efficiency of which should theoretically be limited by recombination in the quasi-neutral region [7,20].…”
Section: Discussionmentioning
confidence: 97%
“…It can happen due to the diffusion of the atomic elements into the Cu vacancies in the CIGS absorbers, like the Zn diffusion from the ZnS passivation layer [21] or the removal of Cu from the interface and occupation of potassium in the KF treatment [10]. An appropriate etching completely removes the surface oxides before the chemical bath deposition of the buffer layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation